Exploring Extension Agent Capacity and Readiness to Adopt Policy, Systems and Environmental Change Approaches - Washburn, Lisa; Norman-Burgdolf, Heather; Jones, Natalie; Kennedy, Lauren E.; Jarvandi, Soghra (Frontiers in Public Health, 2022)
Introduction Enhanced Extension outreach strategies combine traditional direct education programs with public health approaches like policy, systems, and environmental (PSE) change. However, the Cooperative Extension system and county-based Family and Consumer Sciences (FCS) Extension agents have historically prioritized direct education programming and diffusion of enhanced outreach strategies has varied. Extension personnel may lack capacity and readiness for successful PSE change implementation. This study explored perceived acceptability, capacity, and readiness for PSE change work among FCS Extension agents in two states. Method A survey was developed framed by selected domains from the Consolidated Framework for Implementation Research: Intervention Characteristics, Inner Setting, Characteristics of Individuals, and Process. All questions utilized a 5-point Likert scale, except for an item examining respondents' stage of change regarding PSE change strategies. Descriptive statistics and response frequencies for all variables were calculated. Results Survey responses (n = 116) indicated PSE change work was perceived as valuable. Potential barriers included perceived complexity, organizational readiness issues (e.g., reporting and evaluation structures; performance incentives), and worries about stakeholder responses in shifting away from direct education. Responses indicated self-efficacy for skills important in implementing PSE change. Most respondents (53%) indicated being at the pre-contemplation or contemplation stage of change in pursuing PSE change work. Discussion Combining PSE change strategies and direct education programming allows Extension to do what it does best – provide effective programs to improve and sustain health and wellbeing of individuals and families. Findings are informative for others aiming to build capacity within community educators, Extension and public health professionals to implement PSE change.